Implementasi Program Standar Kecakapan Ubudiyah dan Akhlaqul Karimah (SKUA) dalam Membentuk Karakter Religius Peserta Didik Madrasah Ibtidaiyah - Kusnul Munfa'ati; Dewi Murtasia; Irma Putri Anggraini; Suci Syamrotul Ilmiya (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The lack of attention to the quality of worship poses a significant challenge in character education in Indonesia. This study focuses on the implementation of the Standard Program for Ubudiyah and Akhlaqul Karimah (SKUA) in shaping the religious character of students at MI Pancasila Mojosari. Utilizing a qualitative field-based approach, the research collects primary and secondary data through observations, interviews, and documentation. Data analysis follows the framework proposed by Miles and Huberman, including data reduction, data presentation, and conclusion verification. The findings indicate that the SKUA program has a significant impact on enhancing the quality of worship and akhlaqul karimah among students, including increased sincerity in daily worship and improved behavior, such as polite speech and actions aligned with religious values. Data validity is ensured through triangulation and peer discussions to confirm the reliability of the results. These findings offer valuable insights for the development of more effective character education programs at MI Pancasila Mojosari.